Teknologi Virtual Reality (VR) dalam Manajemen Nyeri pada Pasien Kanker - Tulangow, Indri Winny; gayatri, Dewi; Edison, Chiyar; Waluyo, Agung (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the effectiveness of Virtual Reality (VR) technology in pain management in cancer patients. The method used in this research is a systematic review where this article is searched through online databases, namely Science Direct, Scopus, Sage Journals and ProQuest. The results of research from ten articles show that the use of VR technology in pain management in pediatric and adult cancer patients, both in the process of making a diagnosis and in surgery and chemotherapy or radiation therapy, shows a significant reduction in pain scale. In conclusion, the use of virtual reality technology is not only effective but also safe and efficient for use in pain management in cancer patients, providing assurance about its application. Keywords: Cancer, Pain, Pain Management, Virtual reality